Ultrasound-guided fascia iliaca compartment block versus intravenous analgesia in geriatric hip fractures: a systematic review and meta-analysis of randomized trials demonstrating superior pain control - Liu, Chang; Han, Shunyu; Wei, Ai; Yang, Lina; Yang, Mengchang (Frontiers in Medicine, 2025)
BackgroundSevere pain in elderly hip fracture patients exacerbates perioperative risks. This meta-analysis compares ultrasound-guided fascia iliaca compartment block (UG-FICB) with intravenous analgesia for pain management.MethodsA comprehensive search of randomized controlled trials (RCTs) published through February 2025 was conducted across major databases, including English-language databases and Chinese databases. Outcomes analyzed via RevMan 5.3 using random/fixed-effect models. Primary outcomes encompassed Visual Analog Scale (VAS) scores, analgesic consumption, patient satisfaction, main adverse reactions, and gastrointestinal adverse events. Secondary outcomes included intraoperative blood loss, operative time, length of stay, and respiratory adverse events.ResultsA total 26 RCTs (n = 2,347), UG-FICB significantly not only reduced Visual Analog Scale (VAS) scores at all timepoints: 0.5 h (p = 0.02), 2 h (p = 0.001), 4 h (p = 0.002), 6 h (p < 0.00001), 12 h (p = 0.0002), 24 h (p < 0.00001), and 48 h postoperatively (p = 0.003), but also reduced postoperative analgesic consumption (OR = 5.27, p < 0.00001). Patients receiving UG-FICB exhibited fewer drug-related adverse events, including dizziness (OR = 2.34), hypersomnia (OR = 3.58), and gastrointestinal complications (nausea OR = 2.57; constipation OR = 4.82; p < 0.05). UG-FICB also shortened length of stay (MD = 1.88 days, p < 0.00001) and enhanced satisfaction (OR = 0.26, p = 0.0002).ConclusionCompared to intravenous analgesia, UG-FICB provides superior, sustained pain relief with fewer opioid-related complications and higher patient satisfaction. UG-FICB’s safety and efficacy advantages strongly support its adoption as first-line therapy in geriatric hip fractures protocols.